BROADCAST MEDIA ORGANISATIONAL INTEROPERABILITY FACTORS AS DETERMINANTS OF COMMUNAL CONFLICT MANAGEMENT IN OYO AND LAGOS STATES, NIGERIA
Communal conflicts are on the increase in Nigeria with attendant negative consequences. The reportage of these conflicts brings about constraints in their management and sometimes aggravates the situation. This necessitates the interoperability of the broadcast media organisations in their reporting to enhance information sharing and consistency. Previous studies have focused more on different strategies used in Communal Conflict Management (CCM), while few have considered the contributions of interoperability factors among the broadcast media in managing such conflicts. This study, therefore, determined Broadcast Media Organisational Interoperability Factors (BMOIF) as predictors of communal conflict management in Oyo and Lagos states, Nigeria. It also examined the effectiveness of the broadcast media. The study adopted survey design. Oyo and Lagos states were purposively selected because of the presence of federal, state and privately owned media organisations. Three radio and television stations were purposively selected from each of the two states. ‘Amuludun’, Broadcasting Corporation of Oyo State (BCOS), and Splash FM radio stations, and Nigeria Television Authority (NTA), BCOS and Galaxy television stations in Oyo State; and Bond FM, Radio Lagos, Raypower FM radio stations and NTA Lagos, Lagos Television and Television Continental from Lagos State. Stratified random sampling technique was adopted in selecting 303 broadcast journalists; 958 community representatives from four (two from each state) purposively selected high conflict-prone local government areas. Media Personnel and Audience CCM Checklists, BMOIF (r=0.97) and Broadcast Media Effectiveness (BME) (r=0.99) scales were used for data collection. These were complemented with 12 and eight sessions of In-depth Interview and Focus Group Discussion respectively with selected journalists and community representatives. Data were subjected to content analysis, descriptive statistics, Pearson product moment correlation and multiple regression at 0.05 level of significance. Usage of interoperable communication (r=.87), technology (r=.86) and training (r=.85) had positive significant correlation with CCM while governance and standard operating procedure did not. The BMOIF significantly predicted CCM (F(5, 297)=194.64, R=.88); accounting for 76.6% of its variance. Usage of interoperable communication (β=.49) and technology (β=.27) had relative significant contributions to CCM while governance, standard operating procedure and training had none. The BME indices had relative significant contributions to CCM as follows: programme timing (β=.71), programme content (β=-.58) and audience reach (β=.35) while language, news coverage area, frequency of programme and reception had none. About 62.0% of Lagos State respondents indicated Television Continental as the most effective broadcast station that disseminated programmes that promote CCM and 59.8% indicated Splash FM in Oyo State. The challenges affecting broadcast media interoperability were: incessant power failure ( x ̅=3.21), telecommunication network failure (x ̅ =3.17), inadequate funding ( x ̅ =3.17), inadequate protection of journalists ( x ̅ =3.09) and old communication equipment (x ̅ =3.05). Although there were perceived advantages of interoperability in terms of easy interpersonal communication, online streaming of news; yet there was inadequacy of training opportunities. Usage of interoperable communication and technology positively influenced the management of communal conflicts in Oyo and Lagos states. There is a need to improve their usage to enhance the use of broadcast media organisations in communal conflict management.